Platelet, Plasma, Urinary Tryptophan-Serotonin-Kynurenine Axis Markers in Hyperacute Brain Ischemia Patients: A Prospective Study - Saccaro, Luigi F.; Pico, Fernando; Chadenat, Marie-Laure; Richard, Olivier; Launay, Jean-Marie; Bastenaire, Brigitte; Jullien, Philippe; Lambert, Jerôme; Feuga, Vincent; Macquet, Maryline; Callebert, Jacques; Lambert, Yves; et al. (Frontiers in Neurology, 2022)
Background and Purpose: Ischemic stroke is one of the most common causes of morbidity and mortality and has numerous clinical mimics. Previous studies have suggested a potential role of the tryptophan-serotonin (5-HT)-kynurenine (TSK) axis in ischemic stroke. Studies assessing this axis in the hyperacute phase of ischemic stroke (<4.5 h) are lacking. This prospective study thus evaluates the TSK axis in transient ischemic attack (TIA) and hyperacute ischemic stroke (AIS) patients. Methods: This study included 28 patients (24 AIS and 4 TIA) and 29 controls. The blood and urine samples of patient were collected within 4.5 h of symptoms onset (day 0, D0), then at 24 h and 3 months. Control blood and urine samples were collected once (D0). The TSK axis markers measured were platelet serotonin transporter (SERT) and 5-HT2A receptor (5-HT2AR) densities and platelet, plasma, and urinary 5-HT, plasma and urinary 5-hydroxyindole acetic acid (5-HIAA), and plasma kynurenine and tryptophan (TRP) levels. Results: At D0, patients exhibited a lower (p = 10−5) platelet SERT density, higher (p < 10−6) platelet 5-HT2AR density, higher (p = 10−5) plasma kynurenine/tryptophan (K/T) ratio, and higher urinary 5-HT (p = 0.011) and 5-HIAA (p = 0.003) levels than controls. Conclusions: We observed, for the first time, a hyperacute dysregulation of the serotonergic axis, and hyperacute and long-lasting activation of the tryptophan-kynurenine pathway in brain ischemia.